Galangin Regulates Oxidative Stress Levels in Porcine Embryos Through Interaction with the Neh1 Domain of Nrf2 - Zhi-Chao Chi; Shu-Ming Shi; Li-Ying Liu; Lin-Yi Qu; Jing-Hang Li; Guan-Lin Jia; Yu-Yan He; Lin-Xuan Li; Yong-Xun Jin; Ming-Jun Zhang; Xian-Feng Yu (Antioxidants)
Oxidative stress poses a challenge to in vitro embryo culture. As a flavonoid, galangin (GAL) has been shown to have antioxidant effects, but the effect and antioxidant capacity of GAL in the in vitro development of porcine parthenogenetic embryos are still unknown. In this study, we demonstrated that 1 µM GAL significantly increased the blastocyst rate, decreased the accumulation of intracellular reactive oxygen species (ROS), increased the glutathione (GSH) level, and enhanced mitochondrial function in early porcine embryos. Nuclear factor erythroid-2-related factor 2 (Nrf2) was identified as the target gene of GAL via network pharmacology, and the transcript levels of related antioxidant enzymes (HO-1, NQO1, SOD2, and CAT) were found to be increased. Since Nrf2 has seven domains, we constructed Nrf2 mutants lacking different domains in vitro. We found that GAL specifically binds to the Neh1 domain of Nrf2. Subsequent embryonic experiments demonstrated that the antioxidant effect of GAL was abolished after Nrf2 deletion. These results suggest that GAL can directly bind to Nrf2 to regulate the level of oxidative stress and improve mitochondrial function in embryos.